Procurement procedures under the Private Finance Initiative: the operation of the new legal framework - Craven, Richard (2012)
The PhD research is concerned with how EU procurement regulation impacts upon the procurement process for Public-Private Partnership (PPP) projects. The process followed to award the contract and to set the terms of the agreement in the procurement of a PPP project (invariably highly sophisticated arrangements) is crucial for value for money. Prior to 2004 the process was regulated by EU legislation designed in the 1970s, which failed to adequately cater for modem procurement methods, like PPPs. Thus new legislation in 2004 introduced a new procedure for these projects: competitive dialogue. However, commentators have identified possible problems with competitive dialogue and there are numerous legal grey areas. The research examines the way in which the new legal framework for competitive dialogue is applied to PPPs in the UK, and actors' perceptions of the framework. It seeks to identify perceived positive aspects of competitive dialogue in facilitating best practice; perceived problems, including any legal uncertainty and constraints on best practice; strategies to conduct the process within the constraints; and the factors that influence compliance and approach to legal risk. The research adopts a socio-Iegal approach, combining analysis of the legal rules, with a study of the literature on theories of regulation and enforcement, and qualitative interviews with legal advisors, procurement officers, and policymakers.